DO MIGRANTS’ REMITTANCES DRIVE FINANCIAL INCLUSION IN NIGERIA? - MUSTAPHA-JAJI, OLAIDE KAFAYAT; ADESINA-UTHMAN, GANIYAT A (JOURNAL OF ECONOMICS AND ALLIED RESEARCH, 2023)
Migrants’ remittances have increased tremendously over the past years in comparison to other capital flows but the level of financial inclusion in Nigeria has been unimpressive. Therefore, this study analyzed the relationship between migrants’ remittances and financial inclusion in Nigeria for the period 1981 to 2021. The study employed secondary data which were analyzed using the auto-regressive distributed lag estimation techniques. The ARDL estimate showed that migrants’ remittances is a significant determinant of financial inclusion in Nigeria. Thus, the study concluded that migrants’ remittance played an important role in enhancing financial inclusion in Nigeria. Consequently, the study recommended the need for increase expansion of bank branches in the remote and rural regions of the country. This will contribute to the growth of financial inclusion in Nigeria. More so, provision of more stable power supply in the remote and rural areas would enhance mobile and internet banking thereby contributing to the growth of financial inclusion in Nigeria.